UNJUK KERJA PENERAPAN TEKNOLOGI VoIP PADA JARINGAN VPN (VIRTUAL PRIVATE NETWORK) - Hadria Octavia (Elektron : Jurnal Ilmiah, 2013)
VoIP ( Voice over Internet Protocol ) is a technology used for communication in the form of IP based voice media over long distances. The concept of a VPN (Virtual Private Network) in this paper makes a client that is on the public network can be connected to a LAN network. To use the VoIP server in the Linux operating system Trixbox, whereas for the VPN server using ClearOS and X-lite is used as a softphone to make calls to the client. Of testing at 64kbps bandwidth using the G711 codec produces value performance (delay, jitter, and packet loss ) is not good, so that voice data delivered is less clear. Thus the choice of bandwidth for the G.711 codec 512kbps up is the best solution to get the value of the performance (delay, jitter, and packet loss) better . And a choice of 3 Greed (low, medium, high) on setting bandwidth, high is the best option. Because it can produce the best performance for VoIP VPN technology.